Marketing strategies for the livelihood income generating activities in the post war marketing context - Velnampy, T.; Kajendra, K.; Shivany, S. (University of Jaffna, 2012)
Absence of research on small business which significantly contributing factor to strategic marketing, and small! Business research domain, and the extant research on marketing strategies lacks in theory based frameworks that explicate what marketing strategies are appropriate for the livelihood Income Generating Activities (LIGAs) in the post war marketing context. Present study explored marketing strategies for LIGAs in the unique context. Using grounded theory approach, data were collected from 10 focus group discussions with different LIGAs. This study compared the LIGAs which do well and which failed to attain their objectives. Customer relationship, customer orientation, joint ventures, word of mouth promotion, overall cost leadership, and course related marketing has been identified as the marketing strategies which have been adopted by the LIGAs, which have succeeded in their business, Branding was identified as a strategy which has to be considered for more effective results from LIGAs in the post conflict marketing context.
Keywords: Livelihood; Marketing strategies; Post-War Context; Grounded theory